2022
DOI: 10.1002/alr.23071
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term quality‐of‐life impairment in patients with more than 1‐year COVID‐19–related olfactory dysfunction

Abstract: Long-term quality-of-life impairment in patients with more than 1-year COVID-19-related olfactory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…SF‐36 scores were all within the normal range 48 in the normosmic group while these were reduced in the dysosmics for the health domains “role limitation due to emotional problems,” “energy/fatigue,” “emotional wellbeing,” “social functioning,” and perceived “general health.” Moreover, a weak but significant positive correlation was observed between the SF‐36 domain “energy/fatigue” and the S'S scores suggesting that an improvement in the olfactory scores (i.e., olfactory recovery) is associated with an increased level of energy and, thus, a QoL improvement. This further confirms our previous results on a smaller population 49 …”
Section: Discussionsupporting
confidence: 93%
“…SF‐36 scores were all within the normal range 48 in the normosmic group while these were reduced in the dysosmics for the health domains “role limitation due to emotional problems,” “energy/fatigue,” “emotional wellbeing,” “social functioning,” and perceived “general health.” Moreover, a weak but significant positive correlation was observed between the SF‐36 domain “energy/fatigue” and the S'S scores suggesting that an improvement in the olfactory scores (i.e., olfactory recovery) is associated with an increased level of energy and, thus, a QoL improvement. This further confirms our previous results on a smaller population 49 …”
Section: Discussionsupporting
confidence: 93%
“…Several studies asked binary questions in a concise manner (Coelho et al, 2021 ; Callejón-Leblic et al, 2022 ; Damiano et al, 2022 ; Moideen et al, 2022 ; Turk et al, 2022 ). In other studies, however, questions were less clear or specific (Silverberg et al, 2022 ; Bérubé et al, 2023 ; Pendolino et al, 2023 ). For instance, Hosseininasab et al ( 2021 ) asked participants about the presence of parosmia and phantosmia during longitudinal consultations and telephone interviews in Farsi.…”
Section: Resultsmentioning
confidence: 92%
“…We appreciate Dr. Hyun Jin Min's interest in our article on long‐term quality‐of‐life impairment in patients with more than 1‐year coronavirus disease 2019 (COVID‐19)–related olfactory dysfunction (OD) 1 …”
Section: Figurementioning
confidence: 99%
“…To the Editor: We appreciate Dr. Hyun Jin Min's interest in our article on long-term quality-of-life impairment in patients with more than 1-year coronavirus disease 2019 (COVID-19)-related olfactory dysfunction (OD). 1 In our study, we included only patients with a reported OD. Therefore, we are not able to evaluate the impact of gustatory dysfunction on the quality of life of COVID-19 patients without OD.…”
mentioning
confidence: 99%
See 1 more Smart Citation